HCC EV ECG score: An extracellular vesicle‐based protein assay for detection of early‐stage hepatocellular carcinoma. Issue 3 (17th March 2023) - Sun, Na; Zhang, Ceng; Lee, Yi‐Te; Tran, Benjamin V.; Wang, Jing; Kim, Hyoyong; Lee, Junseok; Zhang, Ryan Y.; Wang, Jasmine J.; Hu, Junhui; Zhang, Zhicheng; Alsudaney, Manaf S.; et al.
Abstract : Background and Aims: The sensitivity of current surveillance methods for detecting early‐stage hepatocellular carcinoma (HCC) is suboptimal. Extracellular vesicles (EVs) are promising circulating biomarkers for early cancer detection. In this study, we aim to develop an HCC EV‐based surface protein assay for early detection of HCC. Approach and Results: Tissue microarray was used to evaluate four potential HCC‐associated protein markers. An HCC EV surface protein assay, composed of covalent chemistry‐mediated HCC EV purification and real‐time immuno‐polymerase chain reaction readouts, was developed and optimized for quantifying subpopulations of EVs. An HCC EV ECG score, calculated from the readouts of three HCC EV subpopulations (E pCAM + CD63 +, C D147 + CD63 +, and G PC3 + CD63 + HCC EVs), was established for detecting early‐stage HCC. A phase 2 biomarker study was conducted to evaluate the performance of ECG score in a training cohort ( n  = 106) and an independent validation cohort ( n  = 72). Overall, 99.7% of tissue microarray stained positive for at least one of the four HCC‐associated protein markers (EpCAM, CD147, GPC3, and ASGPR1) that were subsequently validated in HCC EVs. In the training cohort, HCC EV ECG score demonstrated an area under the receiver operating curve (AUROC) of 0.95 (95% confidence interval [CI], 0.90–0.99) for distinguishing early‐stage HCC from cirrhosis with a sensitivity of 91% and a specificity of 90%. The AUROCs of the HCC EV ECG score remained excellent in the validation cohort (0.93; 95% CI,  0.87–0.99) and in the subgroups by etiology (viral: 0.95; 95% CI,  0.90–1.00; nonviral: 0.94; 95% CI,  0.88–0.99). Conclusion: HCC EV ECG score demonstrated great potential for detecting early‐stage HCC. It could augment current surveillance methods and improve patients' outcomes. Abstract :